A Search for Hot Subdwarf Companions to Rapidly-Rotating Early B Stars. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Peters, Geraldine J.; Gies, Douglas R.; Wang, Luqian; Grundstrom, Erika D.
Abstract: We continue to search for O-type subdwarf companions in binary systems containing Be primaries. We were not able to confirm an sdO object in π Aqr and HR 2142, even though optical and UV observations suggest their presence. Some possible reasons are enumerated.